Effect of chemical degradation followed by toothbrushing on the surface roughness of restorative composites - Fernanda Regina Voltarelli; Claudia Batitucci dos Santos-Daroz; Marcelo Corrêa Alves; Andrea Nóbrega Cavalcanti; Giselle Maria Marchi (University of São Paulo, 2010)
OBJECTIVES: The aim of the present study was to assess the effect of the exposure to food-simulating liquids prior to brushing simulation on the surface roughness of five composite materials (Quixfil, Filtek Supreme, Esthet-X, Filtek Z250, Tetric Ceram). Material and METHODS: Twenty cylinders (5 mm diameter and 4 mm height) of each composite were randomly allocated to 4 groups (n=5), according to the food-simulating liquid in which they were immersed for 7 days at 37°C: artificial saliva, heptane, citric acid, and ethanol. After this period, the top surface of composite cylinders was submitted to 7,500 brushing cycles (200 g load). Measurements of the surface roughness (Ra, ¼m) were carried out before and after the exposure to the chemicals/brushing simulation. Changes on the morphology of composite surfaces were observed through scanning electron microscopy (SEM). RESULTS: The statistical analysis (ANOVA with cofactor / Tukey's test, α=5%) detected a significant interaction between solutions and composite resins. Esthet-X, Filtek Z250 and Tetric Ceram were not affected by the food-simulating liquids/toothbrushing. Citric acid and ethanol increased the surface roughness of Quixfil and Filtek Supreme, respectively. SEM images corroborate the surface roughness findings, demonstrating the negative effect from chemical solutions and mechanical abrasion. CONCLUSIONS: The surface roughness of composite resin materials are differently affected by the food-simulating solutions, depending on the immersion media.